Frying Quality of Some Edible Oil Blends Based on Palm Olein - Shakak, Mahdi A. Saad; A, A. Haleem Raham; faki, Ahmed A. El (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Palm olein was blended with three Sudanese edible oils namely cottonseed, groundnut, and sunflower oils, at two levels (3:1; 1:1, respectively), exposure to frying temperature at 180 ± 20C for 5, 10 and 15hrs and acceptability tests of potato chips fried in such blends were carried out. In the acceptability tests, the sequence of preference of potato chips fried in palm olein blends showed that palm olein / sunflower oil (1:1; 3:1) blends, was similar to the pure palm olein in having first preference in color, flavor and taste, followed by chips fried in palm olein / cottonseed oil blends, whereas the chips fried in palm olein / groundnut oil blends received the least acceptability.